Analisis Faktor Faktor Yang Mempengaruhi Penerapan Digitalisasi Akuntansi Pada Usaha Mikro Kecil Menengah di Kota Batam - Nadiah Indriyani; Erni Yanti Natalia (Peneliti.net, 2023)
Using the UTAUT approach, this study aims to identify the factors that influence the application of accounting digitization to micro and medium enterprises in Batam City. With 259 research samples, this study used an associative quantitative approach. Multiple linear regression analysis was used as the analysis method. SPSS 26 statistical software was used. According to the findings of the t-test research, performance expectations have a 2,414 > 1,969 positive effect on the decision to implement accounting digitization, with a sig t value of 0,013< 0,05 Effort expectations have a negative effect on the decision to implement accounting digitization by - -0,656 < 1,969 with a sig t value of 0,513 < 0,05 Social influence has a 2.384 > 1.969 positive effect on the decision to implement accounting digitization, with a sig t value of 0,018 <0,05. facilitating conditions did not have a positive effect on the decision to implement accounting digitization by 0,966 > 1,969 with a sig t value of 0,335 <0,05 trust perception has a positive effect on the decision to implement accounting digitization by 3,915 > 1,969 with a sig t value of 0,000 < 0,05 business scale has a positive effect on the decision to implement accounting digitization by 3,951 > 1,969 with a sig t value of 0,000 < 0,05